(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
An increased demand for fish, combined with ever-growing global populations our oceans cannot keep up with the rate at which we are fishing our seas. As coastal fisheries declined, fishing started to expand into using open oceans as a resource leading to an 80% decline in bluefin tuna (Thunnus thynnus) and swordfish (Xiphias gladius) in just 5 years. Though overfishing for specific species can be beneficial, and even more surprisingly it’s encouraged. Off the coast of America, a new threat has been growing in recent years, the red lion fish (Pterois volitans). This species originally native to coral reefs in the South Pacific has recently found a new home the Atlantic Ocean. Target fishing the Lionfish will not only help reduce population size, minimize the chances of the Lion fish causing greater ecological damage on the Atlantic Ocean. Is moving public perception and demand towards invasive the next steps in protecting our fisheries? Res. Agric., Livest. Fish.6(3): 397-404, December 2019